2010
DOI: 10.3109/10408444.2010.499504
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis-based weight of evidence: A tool for evaluating and communicating uncertainties and inconsistencies in the large body of evidence in proposing a carcinogenic mode of action—naphthalene as an example

Abstract: (2010) Hypothesis-based weight of evidence: A tool for evaluating and communicating uncertainties and inconsistencies in the large body of evidence in proposing a carcinogenic mode of action-naphthalene as an example, Critical Reviews in Toxicology, 40:8, 671-696, DOI: 10.3109/10408444.2010 R E V I E W A R T I C L EHypothesis-based weight of evidence: A tool for evaluating and communicating uncertainties and inconsistencies in the large body of evidence in proposing a carcinogenic mode of action-naphthalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 55 publications
0
50
0
Order By: Relevance
“…Based on an evaluation of mode of action, Cruzan et al (2009) concluded that these tumors arose as a secondary consequence of the generation of cytotoxic metabolites of CYP2F2 in nasal and lung tissue in mice and CYP2F4 in nasal tissues in rats. Rhomberg and colleagues (2010) explored the hypothesis-based weight of evidence analysis of the naphthalene data in more detail and essentially reached the same conclusions as Cruzan et al (2009), although they could not definitively rule out the involvement of other CYPs such as CYP2E1 and/or other biochemical events such as GSH depletion (Rhomberg et al 2010). Overall, the underlying cancer mechanism, particularly with regard to the proposed involvement of CYP2F enzymes for cumene, naphthalene, styrene, and other similar chemicals remains under investigation, and its relevance to humans is controversial (Cruzan et al 2009, Rhomberg et al 2010).…”
Section: Aromatic Solvents (C9-c12)mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on an evaluation of mode of action, Cruzan et al (2009) concluded that these tumors arose as a secondary consequence of the generation of cytotoxic metabolites of CYP2F2 in nasal and lung tissue in mice and CYP2F4 in nasal tissues in rats. Rhomberg and colleagues (2010) explored the hypothesis-based weight of evidence analysis of the naphthalene data in more detail and essentially reached the same conclusions as Cruzan et al (2009), although they could not definitively rule out the involvement of other CYPs such as CYP2E1 and/or other biochemical events such as GSH depletion (Rhomberg et al 2010). Overall, the underlying cancer mechanism, particularly with regard to the proposed involvement of CYP2F enzymes for cumene, naphthalene, styrene, and other similar chemicals remains under investigation, and its relevance to humans is controversial (Cruzan et al 2009, Rhomberg et al 2010).…”
Section: Aromatic Solvents (C9-c12)mentioning
confidence: 99%
“…Rhomberg et al (2010) concluded that the tumors were most likely the consequence of a cytotoxic (or dual cytotoxic/genotoxic) mode of action although a genotoxic mode of action could not be ruled out. As Rhomberg pointed out, the choice of mode of action is directly related to human relevance as humans…"have insufficient metabolic activation to the naphthalene epoxide to deplete GSH or to create sufficient levels of reactive metabolites so as to produce cytotoxicity, genotoxicity, or both, and without such toxicity, no carcinogenic risk is induced" (Rhomberg et al 2010). Gagnaire et al (1990Gagnaire et al ( , 1991Gagnaire et al ( , 1992 reported that 1,2-diethylbenzene (1,2-DEB) produced a characteristic neurological effect in mice, whereas the other two diethylbenzene isomers (1,3-DEB, 1,4-DEB) were not neurotoxic.…”
Section: Naphthalenementioning
confidence: 99%
See 1 more Smart Citation
“…To determine which study is most appropriate and most consistent with the weight of evidence (WoE), a WoE analysis should be conducted. There are many WoE frameworks available (e.g., Krimsky 2005;ECETOC 2009;Linkov et al 2009;Rhomberg et al 2010;USEPA 2010;Rhomberg et al 2011). The HBWoE framework we used in the Prueitt et al (2011) analysis incorporates several aspects of many of the others and can be summarized in seven steps:…”
Section: Hypothesis-based Weight-of-evidence Evaluationmentioning
confidence: 99%
“…We agree that widely endorsed weight-of-evidence methods are not readily available; indeed, several of us have publicly addressed this very lack and have proposed approaches that might be appropriate for endocrine disruption evaluation (e.g. Borgert et al, 2011;Rhomberg et al, 2010). We cited the WHO/IPCS (2002) approach to this question because, first, it seemed a reasonable approach that would be appropriate to the present case and, second, the SOTA ED itself suggested it was following this approach.…”
mentioning
confidence: 99%